Thinking big and scaling up : insights from Fazle H. Abed, founder and chairperson of BRAC - Abed, Fazle; ASHOKA's Global Academy for Social Entrepreneurship; SKOLL Foundation (ASHOKA (Innovators for the Public)., 2006)
Abed in this video examines the challenges of building an organization with enough scale to have global impact, but with enough local knowledge and support to be effective. He offers inavaluable advice on operational issues, such as staff training and sustainable revenue streams, that ensure viable, broad, and long-lasting change.
DVD.
Keywords: Entrepreneurship -- Social change; New business enterprises -- Management; Organization -- Management; Social entrepreneurship; Social responisbility of business